2017
DOI: 10.3233/mnm-16116
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and antioxidant properties of eleven wild edible plants from Assam, India

Abstract: The aim of this study was to examine the phytochemicals and antioxidant properties of eleven wild edible plants from Assam of North-East India. The phytochemical study indicated the presence of several medicinally active compounds in the methanolic extracts of plants. Evaluation of antioxidant activities were done by DPPH, ABTS, H 2 O 2 and FRAP assays. The investigation revealed antioxidant activities with DPPH IC 50 value ranging from 135.0 ± 1.49 g/mL (L. javanica) to 516.34 ± 2.52 g/mL (B. lanceolaria), AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Utilization of these compounds has become widespread to minimize occurrence of common non-communicable diseases in adults. Plant-based foods contain many phytochemical compounds along with nutrients such as proteins, fats, carbohydrates, vitamins, and minerals (Narzary et al, 2016). Plant phytochemicals are potent antioxidants against reactive oxygen species and have several health benefits (Narzary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of these compounds has become widespread to minimize occurrence of common non-communicable diseases in adults. Plant-based foods contain many phytochemical compounds along with nutrients such as proteins, fats, carbohydrates, vitamins, and minerals (Narzary et al, 2016). Plant phytochemicals are potent antioxidants against reactive oxygen species and have several health benefits (Narzary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is used as herbal tea 9 , vegetables 10 , insect repellent 11 and used in wounds, injuries, pain and skin infection 12 . This plant has also been reported for antioxidant property 8 . Polygonum perfoliatum L. is locally known as Mwitasikla in Bodo.…”
Section: Introductionmentioning
confidence: 88%
“…It has been reported that P. perfoliatum extracts possess cytotoxicity effects against colon carcinoma, human mammary carcinoma, hepatocellular carcinoma, prostate carcinoma, and erythro-leukaemia cells 13 . It has also been reported that P. perfoliatum have anti-inflammatory 14 , anti-bacterial 15 , and antioxidant properties 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assam, Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland, Tripura and Sikkim is famous for its multi-ethnicity and rich biological resources. The region has very friendly climatic conditions, diversity of plants many of which have their own biological values and the rural and tribal people of the region mostly depend on biological assets for their food, shelter, medicare and other cultural purposes [12][13][14][15]. The Hel river stream of western Assam originates from Bhutan.…”
mentioning
confidence: 99%